Variability in sodium content of takeaway foods: Implications for public health and nutrition policy - Alexandra Irina Mavrochefalos; Andrew Dodson; Gunter G. C. Kuhnle (PLoS ONE, 2026)
Background: Excessive sodium intake is a major modifiable risk factor for cardiovascular disease, yet accurately assessing dietary sodium remains challenging due to food composition variability and inaccurate menu labeling. While menu labels are intended to guide consumers, discrepancies between reported and actual sodium content could undermine their effectiveness. Objective: To evaluate the accuracy of menu-declared sodium content in takeaway foods by comparing reported values with laboratory measurements. Design: A cross-sectional analysis of 39 takeaway food items from 23 outlets in Reading, UK. Sodium content was measured using Inductively Coupled Plasma – Mass Spectrometry (ICP-MS) and compared to menu-declared values. Results: Sodium content varied widely across food categories. Median sodium levels ranged from 0.1 g/100g (chips from fish & chips shop) to 1.6 g/100g (pizza), with some meals exceeding the 6 g/day recommended intake in a single serving. Curry dishes exhibited the greatest variability (2.3–9.4 g per dish). Significant discrepancies were found between menu-reported and measured sodium levels, with almost 50% of foods exceeding declared values. Conclusion: Take-away foods exhibit substantial sodium variability, and menu labels often fail to accurately reflect actual sodium content. These findings have implications for nutritional epidemiology, where inaccurate sodium estimates may misclassify intake, and for public health, as misleading labels could hinder sodium reduction efforts. It is therefore important that menu labels are not considered definitive but rather general indicators of sodium content and potentially other nutrients.